2022
DOI: 10.21273/horttech04982-21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Rate, Fertilizer Type, and Application Method on Cabbage Yield and Nutrient Concentrations

Abstract: Georgia is a leading fresh market cabbage (Brassica oleracea var. capitata) producer. Current recommendations for bare-ground cabbage grown in the Coastal Plain of Georgia indicate 175 to 225 lb/acre nitrogen (N). Approximately one-third of N fertilizer is recommended at planting, with two or three additional side-dress applications during the season. Growers have begun banding liquid fertilizer between four and six times during the season to reduce N leaching and enhance productivity. To determine the validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Soil mineral N responses to fertilizer N rate application in the present study were similar to those previously reported in cabbage [21,22], potato [23], bell pepper [24], and even onion [8,25] grown in coarse textured soils during the spring season of southeastern U.S. Results from the present study indicate that the fertilizer N rate of 117 kg of N ha −1 was adequate to sustain soil N availability.…”
Section: Discussionsupporting
confidence: 88%
“…Soil mineral N responses to fertilizer N rate application in the present study were similar to those previously reported in cabbage [21,22], potato [23], bell pepper [24], and even onion [8,25] grown in coarse textured soils during the spring season of southeastern U.S. Results from the present study indicate that the fertilizer N rate of 117 kg of N ha −1 was adequate to sustain soil N availability.…”
Section: Discussionsupporting
confidence: 88%
“…It was previously reported that the increase in the intensity of N nutrition significantly affected the yield of broccoli [26]. Although others have indicated that the N rate does not significantly improve the cabbage yield, it was observed that cabbage fertilised with the lowest N rate (196 kg•ha −1 ) had the lowest yield value [27]. The correlation analysis of our results indicated that the yield of flowering Chinese cabbage was significantly correlated with the N content in the plants from pots (r = 0.87, p < 0.05).…”
Section: Discussionmentioning
confidence: 97%
“…Mineral fertilization and biofertilization are crucial factors shaping the productivity of cabbage. The application of appropriate dosages of fertilizers, considering the specific nutritional requirement of cabbage plants, directly impacts their growth, development, and final quality [28]. Similarly, plant growth-promoting bacteria can influence plant growth and development, thereby impacting overall crop performance.…”
Section: Discussionmentioning
confidence: 99%